Consolidation and Drying Properties of Sewage Sludge - O'Kelly, Brendan (My University, 2005)
The consolidation and air-drying properties of dewatered sewage sludge from Tullamore municipal wastewater treatment plant were studied using soil laboratory tests. Biologically active, and stabilized samples prepared in the laboratory, were consolidated using the oedometer apparatus and the large hydraulic consolidation cell. Index tests, including specific gravity of solids and loss in mass on ignition, were used to quantify the level of biological digestion of the test material. Sludge in the liquid state had a low permeability of the order of 10-9m/s, while consolidated sludge material was practically impermeable. Flocs of mainly organic clay-sized particles, which comprised roughly 90% of the solids, trapped the pore water, resulting in the very low permeability measured. Consolidation largely occurred as a result of creep, and in the long-term, due to decomposition of the solids. Greater levels of biological digestion reduced the organic content and produced a more free-draining material. The application of the test data in engineering the efficient landfill disposal of the sludge material, and predicting the long-term rates of settlement, biogas and leachate generation at the landfill, are presented.
Invited presentation at the Geotechnical Society of Ireland Research Seminar
PRESENTED
University College Dublin, Dublin
Keywords: Sewage